The Use of Lapor! As A Medium for Delivering Citizen Concerns About Public Services to Government - Nurtanzila, Lastria; Prasetya, Aldi Rizal (Jurnal Ilmu Informasi, Perpustakaan, dan Kearsipan, 2018)
The development of information and the rapidly growing digital world have affected all aspects of life, including the public service sector. To make public services more accessible to the community, the Indonesian government has implemented LAPOR!, an e-government application. Citizens can use LAPOR! to submit concerns or complaints regarding public services to the government. The present qualitative study examined the use of LAPOR! as a tool for delivering information to the Indonesian government, using a review of relevant literature and secondary data. The study explores how LAPOR! functions, what features are provided, how citizens have responded to the availability of this tool, and how LAPOR! has served as a form of egovernment that promotes good governance. LAPOR! has been used by 80 government agencies and five local governments. It fulfills both top-down and bottom-up management principles through an integrated system based in the central government that disseminates reports on complaints and investigations to related institutions, local governments, and citizens. Surveys have found that LAPOR! is generally viewed as effective and reliable, with 70% of users indicating that they would continue to submit concerns through this system.